Leveraging IoT and AI Towards Customer-Centricity and Customer Satisfaction in CGD Business in India - Purohit, Santanu; Purohhit, Sujoita; Jain , Arvind Kumar; Mathew , Rejo (RIRAI Publisher, 2025)
The retail petroleum industry is undergoing a significant transformation driven by evolving mobility models, such as shared transportation and renewable energy, rising customer expectations for convenience and personalisation, and the adoption of alternative energy sources. Consumers increasingly demand tailored experiences, and digital technologies are at the heart of meeting these expectations. With rapid technological advancement, customer preferences and buying behaviours are shifting. In the Indian context, factors such as gender, income, and education have a significant influence on technology adoption in the retail fuel sector. Customers are increasingly responsive to technology-driven offerings, such as digital payments, automated fuel quality checks, transaction alerts, and tracking tools, demonstrating a growing acceptance of innovative solutions. This study explored the application of IoT and AI technologies in the City Gas Distribution (CGD) sector, focusing on enhancing customer recognition, personalisation, and satisfaction at fuel retail points. A solution was deployed at a CNG fuel station in Karnataka from August to October 2024, spanning a period of three months. Data collected during this time was analysed to assess the impact. Results revealed a 30% reduction in fueling time and an 81% increase in customer satisfaction, showcasing how technology-driven initiatives can significantly enhance operational efficiency and customer engagement. The integration of IoT and AI not only streamlined station operations but also contributed to improved customer identification, acquisition, and retention, ultimately boosting sales and revenue. This case illustrates the growing importance of digital transformation in the fuel retail sector and highlights the strategic significance of adapting to shifting consumer expectations through innovative technologies.